Sanitary and Environmental Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Major concerns regarding health and the environment are at the heart of the United Nations Educational, Scientific and Cultural Organization's Sustainable Development Goals. Now more than ever, humanity is called upon to take action to protect the environment and public health. The environment in which we live is the most vital factor for our health and well-being. Human activities have significant impacts on the atmosphere, lithosphere, hydrosphere, biosphere, and even outer space. Biological, chemical, and physical risk factors are part of our everyday lives, and scientific research continuously faces challenges to understand and mitigate these interactions to make life on Earth more sustainable. The sustainability of human societies and the biodiversity that supports them requires the responsible supervision of natural resources, including the development of technologies and regulations.